Sunburn Risk at High Altitudes Greater Than Most Realize - Rigel, D. S.
A Rocky Mountain high may come at a steep price for some athletes. Athletes who play and train at high elevations may have about twice the risk of developing nonmelanoma skin cancer than outdoor athletes at sea level at a similar latitude, according to a new study. This risk is substantially greater than previous estimates and greater than most people realize. "We found that the direct UV-B levels at 8500 feet in Vail, Colorado, were approximately 60% higher than at sea level in New York [City]," observes Darrell S. Rigel, MD, of the NYU School of Medicine. "In addition, the direct UV-B levels in Vail were the same as those in Orlando, a site nearly 775 miles closer to the equator." (See Rigel et al., 1999.) Rigel and colleagues used a hand-held meter to measure UV-B radiation in Vail, Orlando, and New York City. They took the readings at noon on cloudless days within 12 days of the March 22, 1998, solar equinox. They found that UV-B intensity rose exponentially with altitude. "This model suggests an approximate 8% to 10% increase of UV intensity for each 1000 feet of elevation across the studied latitudes," note the authors. A 1988 study reported only a 4% change in UV-B intensity per 1000 feet in altitude. The findings suggest that a person of average complexion with unprotected skin would burn after only six minutes of noontime exposure at 11,000 feet in Vail. The same person would develop sunburn after 14 minutes at the lower altitude of 8500 feet in Vail or at sea level in Orlando. It would take 25 minutes for sunburn to develop under these circumstances in New York. Active people need to appreciate the potential risks associated with exposure to sunlight. The year-round popularity of high-altitude sports is soaring. Resorts such as Vail and Sun Valley, Idaho, are nearly as busy with biking, fishing, and golfing in summer as they are with skiing, snowboarding, and snowshoeing in winter. To reduce UV-B damage to unprotected skin, recent guidelines issued by the American Academy of Dermatology suggest that outdoor enthusiasts wear protective clothing, avoid the strongest mid-day sun, and apply sunscreen daily.